IRRIGATION PLANNING FOR ORGANIC VEGETABLE DEVELOPMENT FAMILIA SOLANACEAE BANYUMULEK WNT TECHNO PARK - widiyono, wahyu (Teknologi Indonesia, 2016)
Organic vegetable development on chili, eggplant and tomato, Familia Solanaceae is one programme of Banyumulek Techno Park-LIPI, in the West Nusa Tenggara (WNT). The location is in the lowland area with an altitute aroud less than 100 m above sea level, soil texture is sandy loam with rather fast permeability (2.64 cm hour-1 , D3 climate type according to Oldeman Classification with 4-6 wet months and 3-4 dry months. Annual rainfall are varies from 1.553 mm year-1 and 2.779 mm year-1, with average 1.845 mm year-1. Aim of research are (1) to understand surplus and deficit water condition during a year to cultivate chili, eggplant and tomato; and (2) to understand water volume and irrigation time to irrigate crops in order they do not face water deficit. Research methods were conducted through analysis rate of rainfall and evaporation-evapotranspiration during a year, simulation of water deficit, crops water need and irrigation time. The irrigation planning was used as application guide to cultivate above crops in the Banyumulek, demplot.